KELEWATAN PENGENDALIAN KES FASAKH DALAM ASPEK UNDANG-UNDANG TATACARA MAL: KAJIAN KES DI SELANGOR: Delay of Fasakh Proceedings in Shariah Court Civil Procedure: A Case Study in Selangor - Md Zain@Zakaria, Mohd Zaidi; Abdullah, Raihanah (Jurnal Syariah, 2019)
Studies relating to the weaknesses of the civil procedures in particular on the process of fasakh litigation are still relevant for review and debate. This is due to the fact that there have been complaints and reports lodged by the public over the delay in hearing of fasakh claims under provisions relating to civil procedures. Therefore, the case study was conducted to find out the extent of the issues as a result of the civil procedure in fasakh cases based on three methods of data collection namely observation, interviews and documentation. The results clearly showed that indeed there are factors in the delay of cases involving civil procedures. Whereby, the researcher suggests certain recommendations based on the data collected.